Prime Minister Decree No. 215/2017 On Amending Some Provisions of the Executive Regulations of Decree-Law No. 14/2012 On the Integrated Development of Sinai Peninsula Issued as per Decree of the Prime Minister No. 959/2012 = قرار رئيس مجلس الوزراء رقم 215/2017 بتعديل بعض أحكام اللائحة التنفيذية للمرسوم بقانون رقم 14 لسنة 2012 بشأن التنمية المتكاملة لشبه جزيرة سيناء الصادرة بقرار رئيس مجلس الوزراء رقم 959 لسنة 2012 / Prime Minister - Egypt. Prime Minister (2025)
Decree of the Prime Minister No. 215 of the year 2017 On Amending Some Provisions of the Executive Regulations of Decree-Law No. 14 of the year 2012 On the Integrated Development of Sinai Peninsula Issued as per Decree of the Prime Minister No. 959 of the year 2012 قرار رئيس مجلس الوزراء رقم 215 لسنة 2017 بتعديل بعض أحكام اللائحة التنفيذية للمرسوم بقانون رقم 14 لسنة 2012 بشأن التنمية المتكاملة لشبه جزيرة سيناء الصادرة بقرار رئيس مجلس الوزراء رقم 959 لسنة 2012